Maximing Learning Strategies to Promote Learner Autonomy - Junaidi Mistar (TEFLIN Journal: A publication on the teaching and learning of English, 2001)
Learning a new language is ultimately to be able to communicate with it. Encouraging a sense of responsibility on the part of the learners is crucial for training them to be proficient communicators. As such, understanding the strategies that they employ in acquiring the language skill is important to come to ideas of how to promote learner autonomy. Research recently conducted with three different groups of learners of English at the tertiary education level in Malang indicated that they used metacognitive and social startegies at a high frequency, while memory, cognitive, conpensation, and affective strategies were exercised at a medium frewuency. This finding implies that the learners have acquired some degrees of autonomy because metacognive strategies requires them to independently make plans for their learning activities as well as evaluate the progress, and social strategies requires them to independently enhance communicative interactions with other people. Further actions are then to be taken increase their learning autonomy, that is by intensifying the practice of use of the other four strategy categories, which are not yet applied intensively.